Contribution of root decay process on soil infiltration capacity and soil water replenishment of planted forestland in semi-arid regions - Wu, Gao-Lin; Cui, Zeng; Huang, Ze (Geoderma, 2021)
•Contribution of root decay process on soil water replenishment was assessed.•The macropore formed by decayed root increased the infiltration rate at each stage.•The decayed roots maintain rapid preferential infiltration by reducing root density.•Soil water replenishment significantly increased with root decay ages. Large-scale afforestation has seriously aggravated the consumption of soil water and caused soil desiccation and even the dry soil layers, which has been restricting the survival and sustainability of vegetation in semi-arid areas. How to solve soil water deficit reasonably is an important practical problem we are facing. Here, a field experiment of the decayed roots with different times on soil water infiltration processed was conducted in planted forestland by a double-ring infiltration instrument, to determine the contribution of decayed tree roots on soil water infiltration process and replenishment. Results showed that the decayed process of tree roots in forestland could significantly reduce root density (RD) and increase the relative porosity improved by the roots (RPIR) (P < 0.05). The macropore formed by root decay could not only significantly increase the infiltration rate at each stage (P < 0.05), but also reduce the decrease rate of infiltration rate. Compared with bare land, the decayed roots of the 1–4 yr, the 5–8 yr, and the 9–12 yr increased the amount of soil water replenishment by 37.12%, 217.52%, and 259.85%, respectively. Overall, the decayed tree roots could maintain a relatively high and stable infiltration rate by reduced root density, which increased the effective replenishment of soil water of dry soil layers in forestland. These findings have potential implications for understanding the effect of decay process of tree roots on soil water replenishment, and provide a theoretical basis for the solution to dry soil layers and sustainable management of forestland in semi-arid areas.